2014
DOI: 10.1111/fare.12088
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Development among Low-Income Single Mothers: Potential for Bridging, Bonding, and Building

Abstract: This article explores the potential for community-based social networks to help low-income mothers manage responsibilities of work and family. This 3-year ethnographic study examined the experiences of low-income single mothers participating in an antipoverty program in Boston, Massachusetts, through 73 in-depth interviews. The data refute the claim that bonds within the community hinder women in their attempts to move their families out of poverty. The authors observed benefits from social networks that emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…This article has focused on the reorganization process undertaken by single parents after divorce or separation. Previous research has indicated that single‐parent family systems appear to struggle; such work has tended to focus on the negative effects of divorce on various domains, such as work–life balance (Bakker & Karsten, 2013; Gilleir, 2013), poverty (Maldonado & Nieuwenhuis, 2015), mental health (Symoens, Van de Velde, Colman, & Bracke, 2014), and loneliness (Freeman & Dodson, 2014). Although these are real challenges, over time, as Coltrane and Adams (2003) argued, the dark side of divorce has come to overshadow a more positive side, with studies on the short‐term consequences demonstrating negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This article has focused on the reorganization process undertaken by single parents after divorce or separation. Previous research has indicated that single‐parent family systems appear to struggle; such work has tended to focus on the negative effects of divorce on various domains, such as work–life balance (Bakker & Karsten, 2013; Gilleir, 2013), poverty (Maldonado & Nieuwenhuis, 2015), mental health (Symoens, Van de Velde, Colman, & Bracke, 2014), and loneliness (Freeman & Dodson, 2014). Although these are real challenges, over time, as Coltrane and Adams (2003) argued, the dark side of divorce has come to overshadow a more positive side, with studies on the short‐term consequences demonstrating negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Early evaluations of various group programs to improve low-income mothers’ social networks show promise (Freeman & Dodson, 2014; Lipman et al, 2007; Muzik, Rosenblum, Alfafara, Schuster, Miller, & Waddell, 2015; Pidano & Allen, 2015). An evaluation of a 10-week group focused on offering low-income mothers of young children social support and education indicated that participation significantly improved mood and self-esteem at least short-term (i.e., three months later) compared to mothers in a control group receiving traditional community services (Lipman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 13-week self-care and parenting group for low-income mothers reduced depression, posttraumatic stress, and feelings of helplessness (Muzik et al, 2015). Although these evaluations typically use social relationships and informal support as an intervention coupled with other services (e.g., parenting programs, self-care techniques), initial evaluations, as well as results from this review, suggest that the social dimension of interventions to increase emotional connection and instrumental support is important for maternal and child well-being (Freeman & Dodson, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Feminist family research that was intricately tied to practice also used research methods in which participants helped to co‐construct the analysis. For example, Freeman and Dodson () used a feminist‐informed critical ethnographic approach (interviews and fieldwork) to study oppressed women's experiences from a position of empowerment, “placing the lived experiences of the low‐income single mothers at the center of analysis” (p. 593). The sample consisted of a racially diverse group of women who participated in a community based antipoverty program and probed their perspectives on the benefits (and limitations) of social networking, thereby emphasizing the women's agency and assertiveness in using the resources in their communities.…”
Section: Thematic Analysis Of Trends In Gender Feminist and Intersementioning
confidence: 99%